Noncommutative frames revisited - Cvetko-Vah, Karin (Ars mathematica contemporanea, 2020)
In this note we revisit noncommutative frames. Special attention is devoted to the study of join completeness and related properties in skew lattices.
Keywords: completeness; lattice section; mrežni presek; nekomutativni okvir; noncommutative frame; polnost; poševna mreža; skew lattice